PUBLIC OPINION ON ISSUES OF NATIONAL AND REGIONAL COMPONENT IN THE STATE EDUCATION SYSTEM - Gebekov, G F (History, Archeology and Ethnography of the Caucasus, 2015)
The article covers the results of the opinion polls conducted by the author in 2008, 2012 and 2014 and of the polls taken by other researchers of the national and regional component in the state education system of the Russian Federation (in the context of the Dagestan Republic). Primary focus is on the problem of teaching of native languages, history of Dagestan, culture and traditions of the Dagestan peoples, Dagestan literature, geography of Dagestan, training course on the fundamentals of religious cultures and secular ethics, as well as other problems related to teaching of regional educational subjects in comprehensive and vocational schools. According to the results of the opinion polls, and basing on the monitoring and comparative analysis of public opinion in various social groups of population, the author of the article draws general conclusions and proposes a set of measures aimed at improving the functioning and status of the national and regional component in the comprehensive school.